2012
DOI: 10.1186/1477-7525-10-143
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with health-related quality of life among Chinese caregivers of the older adults living in the community: a cross-sectional study

Abstract: BackgroundUnder the culture of filial piety and due to the Confucianism spirit in China, family caregivers usually undertake the responsibilities of caring for the older adults. They usually suffer from a heavy burden which is believed to impair their mental and physical health. Thus this study aims to describe the health-related quality of life (HRQOL) among Chinese caregivers of the older adults living in the community and explore the predictors of caregivers’ HRQOL.MethodsA cross-sectional study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
66
3
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 34 publications
17
66
3
5
Order By: Relevance
“…The relationship between the caregiver and the care receiver was predominantly a spouse or child, as found in previous studies (18)(19)(20). Daughters-in-law were the caregivers in a significant number of households in our study, as found in studies in India and the Republic of Korea (21)(22)(23).…”
Section: Discussionsupporting
confidence: 75%
“…The relationship between the caregiver and the care receiver was predominantly a spouse or child, as found in previous studies (18)(19)(20). Daughters-in-law were the caregivers in a significant number of households in our study, as found in studies in India and the Republic of Korea (21)(22)(23).…”
Section: Discussionsupporting
confidence: 75%
“…Pior qualidade de vida do cuidador foi associada com pior saúde 29 e maior comprometimento cognitivo do alvo de cuidados. 38 Pior saúde do alvo de cuidados também foi associada com menor nível de felicidade do cuidador.…”
Section: Condições De Saúde Do Alvo De Cuidadosunclassified
“…En un alto porcentaje los cuidadores presentan disminución en su calidad de vida física, emocional y social, la cual esta asociada a una mayor dependencia de la persona que cuidan (22); lo cual se relaciona con otras investigaciones, las cuales afirman que al brindar capacitación para mejorar las habilidades en el cuidado y el manejo de las condiciones especiales mejoran las relaciones con la persona mayor y se fortalecen los lazos familiares (23,24).…”
Section: Discusión Y Conclusionesunclassified